ANALISIS FAKTOR KEUANGAN TERHADAP NILAI PERUSAHAAN JASA TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Falina Aisyah Tasiyah; Laely Aghe Africa (J-MACC, 2022)
This study aimed to analyze and determine liquidity, profitability, leverage and firm size on firm value in transportation service companies. It used dependent variable is company value as proxy of Price Book Value (PBV) and independent variables such as liquidity as proxy of Current Ratio (CR), profitability as proxy of Return on Assets (ROA), leverage as proxy of Debt to Equity Ratio (DER) and company size as proxy of Change in Assets (SIZE). This study uses secondary data obtained from from the Indonesia Stock Exchange (IDX) for the period 2016-2020, with a population of transportation companies listed on the Indonesia Stock Exchange (IDX) with the sample of transportation companies in the period 2016-2020. It was taken by using purposive sampling method, where they were selected based on the criteria. The data were analyzed using a descriptive analysis, classical assumption test and multiple linear regression analysis with SPSS 25. The results indicated that liquidity (CR), profitability (ROA) and company size (SIZE) have no effect on company value, while leverage (DER) has a positive effect on company value.